2017
DOI: 10.21919/remef.v12i3.97
|View full text |Cite
|
Sign up to set email alerts
|

Los beneficios de la inversión socialmente responsable en el desempeño de fondos de pensiones mexicanos

Abstract: Resumen:En el presente artículo se simula el SIEFOREs,el invertir su componente de renta variable socialmente responsables, mismas sustentable (IPCS). Para lograr CONSAR y se recalculó el IPCS a enero de 2004 con el método de capita índice como insumo, se simuló el es emplear el IPCS, el IPCcomp y el IPC maximiza el índice de Sharpe acciones en el IPCS,las SIEFOREs no pierden desempeño logrado ya seacon que si una SIEFORE utilizara el IPCS durante periodos de alta volatilidad emplear los otros dos índices Clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…As a potential source of difference among the indexes that invested in the IPCS vs. the ones that invested in the IPC, is the fact that the base year in which De la Torre and Macias [5] recalculated the The same result, but with slightly wider differences in the short-term, is noted for SB4s (aggressive indexes) in the lower panel of Figure 2. The fluctuation of the SB4 that invested in the IPCS index was wider than the previously simulated ones.…”
Section: Data Processingmentioning
confidence: 75%
See 4 more Smart Citations
“…As a potential source of difference among the indexes that invested in the IPCS vs. the ones that invested in the IPC, is the fact that the base year in which De la Torre and Macias [5] recalculated the The same result, but with slightly wider differences in the short-term, is noted for SB4s (aggressive indexes) in the lower panel of Figure 2. The fluctuation of the SB4 that invested in the IPCS index was wider than the previously simulated ones.…”
Section: Data Processingmentioning
confidence: 75%
“…As noted, there is a lot of literature about the performance of SRI against the conventional or sinful one, but little has been written about the benefits of SRI in the performance of pension fund plans. Only Hongbo, Mitchell, and Piggott [36] have tested whether there is an impact in risk exposure if SRI is included in Japanese pension funds and De la Torre and Macias [5] performed a first test in the Mexican public funds (a test that we extend here). Their results showed that there is a positive contribution to portfolio performance with the use of the IPCS compared with the use of the IPC and IPCcomp, respectively.…”
Section: Literature Review Of the Work That Motivate This Papermentioning
confidence: 99%
See 3 more Smart Citations